Children's Liability in Traffic Criminal Actions (Case Study Decision Number: 273 / Pid.Sus / 2019 / PN Gsk) - Nugraha, Devan Lismatika (UMPurwokerto Law Review, 2021)
This study aims to analyze the court decision number: 273 / Pid.Sus / 2019 / PN Gsk. The method used is normative legal research. The data used is secondary data, including books, scientific journals, research results, and laws and regulations. The data obtained were then analyzed normatively qualitatively. The results of this verdict indicate that first, the defendant M Nastain Bin Kariyanto was proven legally and proven to have committed a criminal act of "Driving a motor vehicle because his negligence resulted in a traffic accident which resulted in another person's death. The defendant's responsibilities are as follows; the defendant is candid, confesses and regrets his actions, the defendant has apologized and made peace with the victim's family, the defendant is polite during the trial, the defendant is not complicated in giving testimony, the defendant admits that he has never acted before, The defendant provided compensation in the amount of Rp. 5,000,000.00 plus motorcycle repair money, because the defendant was able to take responsibility, the defendant had to be declared and therefore sentenced to punishment under what was applicable. Second, the defendant was found guilty and sentenced to criminal law, so based on Article 222 of Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP), Article 310 Paragraph (4) of Law of the Republic of Indonesia Number 22 of 2009 concerning Traffic and Road Transport. Keywords: Children; Accountability; Criminal act